Improving The Self-Efficacy of Post-Stroke Patients Using The Application of Life Review Therapy - Wahyuni, Sri; Prasetyowati, Christina Dewi (Jurnal Keperawatan Soedirman, 2020)
A stroke is a health problem that requires special medical attention, due to its long-term effects such as disability, anxiety, depression, and lack of social participation, which are the causes of patient's self-efficacy being reduced.Â  High self-efficacy is needed so that patients will be motivated to take therapy programs, increase their self-esteem and desire for recovery. The purpose of this study is to determine the self-efficacy improvement of post-stroke patients when provided with life review therapy. This study was quasi-experimental. A purposive sampling technique was used to collect the data, with a sample of 60 respondents (30 controls and 30 interventions). Data was collected using a stroke self-efficacy questionnaire. The statistical tests used were Wilcoxon and Mann Whitney. The patient's self-efficacy in the intervention group showed a change in category in the post-test result (before the intervention it was mostly in the moderate category, after the intervention it wentÂ  into the high category) with statistical test results p=0.00. The control group remained mostly in the moderate category on both pre-test and post-test results with statistical test results p=0.002. There was a comparison of the effectiveness of applying life review therapy between the two groups (p=0.000). The results of this study indicate that the administration of life review therapy can improve the self-efficacy of patients after a stroke.